1300 Transfer of outpatient paediatric prescriptions to primary care via the Electronic Prescription Service (EPS)- community pharmacist views. (17th August 2022) - Traynor, Michael; Kinder, Lauren; Penson, Peter; McCloskey, Alice; Aragon, Octavio
Abstract : Aims: Capture community pharmacists' views regarding the practicalities of dispensing EPS paediatric prescriptions Identify any gaps in specialist paediatric knowledge and training needs required to implement the service fully Determine the most feasible methods for efficient and effective service delivery Methods: University ethical approval was granted (PBS/2021-22/05). An online questionnaire was generated using JISC online survey platform to meet the research aiThe local pharmaceutical committees (LPCs) served as gatekeepers for participant recruitment and circulation of study documentation (participant information sheet and survey link). Pharmacists working within the LPC catchment only were deemed eligible for inclusion. Participants were recruited and questionnaires completed in November 2021. Data was analysed using SPSS statistical package V26. Likert responses were coded 1-5 (uncomfortable-very comfortable) and thematic analysis used for free-text responses. Results: Overall, n= 27 community pharmacists responded of which 14.8% (n=4) were registered independent prescribers. Respondents expressed concerns regarding minimal specialist paediatric training (n= 24, 89%, had no prior specialist paediatric medicine experience). Pharmacists referred to the necessity for additional training and a supporting toolkit prior to service implementation. Although comfortable clinically checking outpatient EPS prescriptions for adults, (n=12, 44.4%) declared discomfort doing this for paediatrics but suggested pre-clinical screening by specialist paediatric pharmacists as safety-netting. Thematic analysis indicated that pharmacists recognised the need for additional information including patient's weight, blood results where relevant, indication for use and other mediation prescribed in order to perform a complete clinical check. Concerns regarding lack of available formulations and stock were highlighted as barriers to supply. An existing technological platform used in community pharmacy, PharmOutcomes, was deemed suitable for effective and efficient service delivery. In line with other community pharmacy services, pharmacists were on board with remuneration as a reward for offering the service. Conclusion: There is a desire for such a prescription transfer process to work but it is essential that this improves the efficiency of the existing service. Pharmacists recognise the benefits of EPS transfer for patients and their carers but in order to facilitate its implementation safely and effectively at a community pharmacy level further paediatric training is required. There is a need for future work to explore this further and capture other key stakeholder views including general practitioners and hospital outpatient teams.